Comparison of Assisted and Unassisted TGT Learning Models Using Playing Cards Media on the Learning Interest of Grade XI Students in Wave Material at Al Bahra Jeneponto Senior High School - Wahyunengsi, Nur; Jusman, Jusman; Ashar, H. Hasbullahair (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The purpose of this study is to determine a) the learning interest of students taught by the TGT Learning Model Assisted by Playing Cards Media b) the learning interest of students taught by the TGT Learning Model Not Assisted by Playing Cards Media c) the difference in Learning Interest of Students taught using the TGT Learning Model Assisted and Not Assisted by Playing Cards Media in class XI on Wave Material at SMAS Al-Bahra Jeneponto. This type of research is Quasi Experimental Design with The Matching Only Post-Test Control Group Design. Design involving the independent variable is the TGT learning model. The population in this study were students of class XI SMAS Al-Bahra Jeneponto who studied science subjects consisting of two classes and totaling 44 students. While the sample was class XI MIPA 1 as the control class and XI MIPA 2 as the Experiment class. The results of descriptive research show that the average value of learning outcomes of students taught using the TGT model without playing cards media is 47.78 and those taught with the TGT learning model assisted by Playing Cards media is 71.95. The results of the Hypothesis testing on students' learning interests showed that there were differences in the learning interests of students taught using the TGT learning model assisted by Playing Cards media.